Joint Modeling of Poverty of Households and Malnutrition of Children Under Five Years from Demographic and Health Survey Data: Case of Rwanda - Habyarimana, Faustin; Zewotir, Temesgen; Ramroop, Shaun (Journal of Economics and Behavioral Studies, 2016)
The main objective of this study was to identify the risk factors associated to malnutrition of children under five years and poverty and assess the correlation between them. We created a composite index from three anthropometric indictors (stunting, underweight and wasting).A multivariate joint model using the generalized linear mixed model was utilized for the analyses of the data. Child age, birth order of the children, the gender of children, birth weights of the children, multiple birth of the child, fever, anemia of the mother, body mass index of the mother, mother’s education level, mother’s knowledge on nutrition, age of household head, source of drinking water, toilet facilities, place of residence of household, source of drinking water and province were found to be significantly related to poverty and malnutrition. The study revealed a positive correlation between poverty of household and malnutrition of children less than five years